Correlation Between Increased Homing Flight Duration and Altered Gene Expression in the Brain of Honey Bee Foragers After Acute Oral Exposure to Thiacloprid and Thiamethoxam - Christen, Verena; Grossar, Daniela; Charrière, Jean-Daniel; Eyer, Michael; Jeker, Lukas (Frontiers in Insect Science, 2021)
Neonicotinoids as thiamethoxam and thiacloprid are suspected to be implicated in the decline of honey bee populations. As nicotinic acetylcholine receptor agonists, they disturb acetylcholine receptor signaling in insects, leading to neurotoxicity and are therefore globally used as insecticides. Several behavioral studies have shown links between neonicotinoid exposure of bees and adverse effects on foraging activity, homing flight performance and reproduction, but the molecular aspects underlying these effects are not well understood. In the last years, several studies showed the effects of exposure to neonicotinoids on gene expression in the brain of honey bees. Transcripts of acetylcholine receptors, hormonal regulation, stress markers, detoxification enzymes, immune system related genes and transcripts of the energy metabolism were altered after neonicotinoid exposure. To elucidate the link between homing flight performance and shifts in gene expression in the brain of honey bees after neonicotinoid exposure, we combined homing flight activity experiments applying RFID technology and gene expression analysis. We analysed the expression of endocrine factors, stress genes, detoxification enzymes and genes linked to energy metabolismus in forager bees after homing flight experiments. Three different experiments were performed. The usefulness of the selected transcripts was confirmed in a pilot study. This first study was followed by a so called “worst-case” study, where we investigated differences in gene expression of fast and slow returning foragers. We found a strong correlation between homing flight time and gene expression pattern. In the third experiment, foragers were exposed in the laboratory and gene expression was analysed without a preceding flight experiment. We could confirm a similar gene expression pattern as observed in the first and second experiment. In addition, we analysed the effect of the feeding mode (group feeding versus single bee feeding) on data scattering and demonstrated that single bee feeding is superior to group feeding as it significantly reduces variability in gene expression transcripts. Based on the data, we thus hypothesize that the disruption of energy metabolism may be the main reason for a prolongation of homing flight time in neonicotonid treated bees.